Improving Care Quality Through a Patient-Centered Medical Journey – Focusing on Children With Early-Onset Scoliosis (International Journal of Studies in Nursing, 2025)
Background: Early Onset Scoliosis (EOS) is a complex and long-term disease requiring a clear treatment journey to meet the needs of patients and improve the quality of care. Constructing a patient-centered medical journey map for EOS patients to provide appropriate medical information is essential. Aim: Controct a patient-centered medical journey map for EOS patients. Subject and methods: Data collection was conducted through team formation, expert-guided workshops, literature review, and patient interviews to develop the medical journey map. Results: The medical journey map covers the entire treatment process, starting from outpatient visits, hospitalization, preoperative examinations, consultations, medical procedures, preoperative explanations, inpatient care, discharge preparation services, and post-discharge follow-up. Conclusion: Constructing a patient-centered medical journey map provides the necessary information and support to patients and their families, enhancing patient satisfaction and healthcare quality.